Konsep dan Prinsip SPMI dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar dan Madrasah Ibtidaiyah : Tinjauan Pustaka - Annisa Nurfadlila Putri Al Ghifari; Adhilia Bunga Deshinta (Universitas Maritim AMNI Semarang, 2024)
The quality of primary education in elementary schools and Islamic elementary schools is a crucial factor in forming the character and skills of the next generation. Education is a fundamental pillar in a country's development. This article examines the Internal Quality Assurance System's (SPMI) ideas and tenets as well as the difficulties in putting it into practice in SD/MI. With an emphasis on ongoing assessment as a way to raise the caliber of instruction, a literature review is the study methodology employed. According on the results, SPMI can assist in determining the advantages and disadvantages of teaching methods and provide suggestions for any necessary enhancements.